Impaired Fibrinolysis in Angiographically Documented Coronary Artery Disease - Adriano Basques Fernandes; Luciana Moreira Lima; Marinez Oliveira Sousa; Vicente de Paulo Coelho Toledo; Rashid Saeed Kazmi; Bashir Abdulgader Lwaleed; Maria das Graças Carvalho (Advances in Hematology, 2015)
Impaired fibrinolysis may predispose to coronary artery disease (CAD). Hypofibrinolysis due to high levels of plasminogen activator inhibitor-1 (PAI-1) has been reported in CAD. A novel regulator of fibrinolytic activity, thrombin activatable fibrinolysis inhibitor (TAFI), has attracted attention in recent years. It acts by blocking the formation of a ternary complex of plasminogen, fibrin, and tissue plasminogen activator (t-PA). Previously ambiguous results regarding TAFI levels have been reported in CAD. We measured plasma levels of PAI-1 and TAFI antigen in 123 patients with age ranging from 40 to 65 years who had been submitted to coronary angiography and assessed the association of these markers with the extent of stenosis in three groups: angiographically normal artery (NAn), mild to moderate atheromatosis (MA), and severe atheromatosis (SA). Plasma levels of PAI-1 were increased in patients with severe atheromatosis compared to mild/moderate atheromatosis or to normal patients (66.60, 40.50, and 34.90 ng/mL, resp.; P < 0.001). For TAFI no difference was found between different groups. When patients were grouped in only two groups based on clinical cut-off point for intervention (stenosis less than or above 70%) we found increased plasma levels for PAI-1 (37.55 and 66.60 ng/mL, resp.; P < 0.001) and decreased plasma levels for TAFI (5.20 and 4.53 μg/mL, resp.; P = 0.04) in patients with stenosis above 70%. No difference was found in PAI-1 or TAFI levels comparing the number of affected vessels. Conclusion. As evidenced by a raised level of PAI-1 antigen, one can suggest an impaired fibrinolysis in stable CAD, although no correlation with the number of affected vessels was found. Curiously, a decreased plasma level of total TAFI levels was observed in patients with stenosis above 70%. Further studies measuring functional TAFI are required in order to elucidate its association with the extent of degree of atheromatosis.